2007
DOI: 10.1016/j.echo.2006.10.012
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Left Ventricular Muscle Bands to Left Ventricular Rotation: Assessment by a 2-Dimensional Speckle Tracking Method

Abstract: Background-Torsion is an essential component of left ventricular (LV) function. Systolic rotation, as a component of torsion, winds the heart muscle up like a spring, setting up recoil for early diastole. We used a new two-dimensional (2D) speckle tracking strain method to study differences in twisting in sub-endocardial and sub-epicardial layers of the left ventricle in open-chest pigs. Our aim was to identify the relative contributions of the inner or outer layers of the LV wall to rotation and hence systole. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 12 publications
3
28
0
Order By: Relevance
“…In this regard, we observed that subendocardial torsion was greater than subepicardial torsion in euthyroid hearts (Fig. 6), and this pattern of regional torsion has been reported in hearts of large mammals (29) and humans (45). LV torsion results from the forces of the endocardial and epicardial muscle layers, which are arranged in opposing helical orientations, and changes in regional torsion can significantly impact overall torsion.…”
Section: In Vivo LV Mechanics After Dobutamine Treatmentsupporting
confidence: 65%
“…In this regard, we observed that subendocardial torsion was greater than subepicardial torsion in euthyroid hearts (Fig. 6), and this pattern of regional torsion has been reported in hearts of large mammals (29) and humans (45). LV torsion results from the forces of the endocardial and epicardial muscle layers, which are arranged in opposing helical orientations, and changes in regional torsion can significantly impact overall torsion.…”
Section: In Vivo LV Mechanics After Dobutamine Treatmentsupporting
confidence: 65%
“…This technique is gaining popularity in publications [40,41] and retains a good correlation with MRI studies [39]. Of particular interest is a publication by Hui et al [42] which studied the contribution to ventricular rotation of the two bundles of myocardial fibers that form the interventricular septum. Because of its wide availabity in comparison with TMRI, speckle tracking echocardiography may become the technique of choice for the determination of AMT at patient's bedside.…”
Section: Discussionmentioning
confidence: 99%
“…The noisy velocities were analyzed by the new method, to produce the LS-STE velocities and the peak rotation and peak circumferential strain values. For the rotating phantoms: a narrow ROI was chosen, encompassing either the inner, middle, or outer layers, thus limiting the measurement to be the average value for a narrow ROI as described by Hui et al [21]. For the small rotating phantom it was possible to apply only two narrow ROIs, so the results of the EchoPAC were compared only to the inner and outer layers.…”
Section: 222mentioning
confidence: 99%
“…The wide ROI was analyzed by the LS-STE program to produce myocardial rotation and circumferential strain values at three myocardial layers. The two narrow ROIs were analyzed by the EchoPAC to produce myocardial rotation and circumferential strain values for the inner half and the outer half of the myocardium as was done by Hui et al [21]. The results of the LS-STE program (three layers) were compared to the results of the EchoPAC (two layers) by: (1) averaging the LS-STE results of the inner and middle layers and comparing it to the inner ROI, analyzed by the EchoPAC.…”
Section: Echocardiography Protocolmentioning
confidence: 99%
See 1 more Smart Citation